A scientific journey from discovery to validation of efficacy in cancer patients: HAMLET and alpha1-oleate. (3rd September 2021) - Ho, James C.S.; Ambite, Ines; Mok, K. H.; Babjuk, Marek; Svanborg, Catharina
ABSTRACT: The protein-lipid complex alpha1-oleate, derived from HAMLET (Human Alpha-lactalbumin Made LEthal to Tumor cells), is identified as a molecular entity with significant therapeutic potential. Structural characterization of the complex and results of a successful placebo-controlled clinical trial are presented.